TRANSMISSION OF AIDS - Sohail, Mian Amjad (Journal of Ayub Medical College Abbottabad, 1988)
AIDS (Acquired Immune Deficiency Syndrome) was first reported in June 1981 by Centre of Disease Control, United States. The epidemic of AIDS which originated in United States has been exported so effectively that the rest of the world is only a bit behind.1 In United States alone more than half a million people are already infected with Human T-cell Iymphotropic virus Type III/Lymphadenopathy associated virus (HTLV-III/LAV) now called Human Immunodeficiency Virus (HIV). Today no country of the world can claim to be free from its deadly clutches. The routes of transmission of AIDS were established well before the causative virus was isolated. It was first described in homosexuals in June 1981.2 It was recognized in intra-venous drug abusers and Haitains3 the following year and by 1983 in recipients of blood and blood products,4 infants born to mothers at risk,5 heterosexual partners of patients with AIDS6 and in Africans.7 These population groups have been included in so-called risk groups.